التكفل النفسي والتأهيل للرياضيين المتعرضين لصدمة نفسية نتيجة الاصابة في حوادث داخل الملاعب - بوهادي حسيبة نورية (كلية العلوم الاجتماعية, 2020)
ملخص الدراسة تهدف هذه الدراسة إلى إبراز دور التكفل النفسي والتأهيل، للرياضيين المصابين بصدمة نفسية بسبب حوادث في المالعب ، واستمرت أعراضها إلى حين تشخيصها الضطرابات ضغوط ما بعد الصدمة، حيث أنها تبقى مهددة للصحة النفسية بصورة مباشرة وغير مباشرة خاصة إن لم يتم التكفل بها، لذلك كانت دراستنا تحاول توضيح طرق التكفل النفسي ودمجها مع التأهيل عن طريق النشاط البدني المكيف. حيث أننا اعتمدنا في دراستنا على المنهج العيادي وقمنا بتطبيق مقياس دافيدسون لقياس كرب ما بعد الصدمة، على أربع حاالت منها اثنان ذكور و اثنان إناث، والتي تم التكفل بهم نفسيا عن طريق العالج المعرفي السلوكي بالموازاة مع التأهيل عن طريق برنامج للنشاط البدني المكيف، كما أننا قمنا ب إعادة تطبيق االختبار بعد فترة العالج، و كان هذا بالعيادة النفسية لديوان مؤسسات الشباب لوالية مستغانم. وقد أظهرت النتائ ج المحصل عليها تحسن الحاالت بشكل ملحوظ وتغيير في العديد من األفكار السلبية واالندماج في المجتمع بصورة ايجابية، وتخفيف أعراض الصدمة النفسية وتجاوزها، وقد تم تأكيد النتائج عن طريق المعالجة اإلحصائية والتي تضمنت اختبار ويلكوكسن واختبار مانويتني، ويعتبران بديال ال معلمي الختبار ت، لمثل هذه الدراسات. وكانت النتائج اإلحصائية تشير إلى وجود فروق بين االختبار القبلي و االختبار البعدي لدى جميع الحاالت في هذه الدراسة، و فروق بين الجنسين لصالح اإلناث، و عدم وجود فروق حسب متغير الخبرة في ميدان الرياضة. ملخص الدراسة د Abstract This study aims to highlight the role of psychological support and rehabilitation for athletes suffering from psychological trauma due to accidents in stadiums, and their symptoms continued until they were diagnosed with PTSD, as they remain directly and indirectly threatening mental health, especially if they are not taken care of, so our study was it tries to clarify methods of psychological support and combine them with rehabilitation through adapted physical activity. Where we relied on the clinical approach in the study and we applied the Davidson scale to measure post-traumatic stress, to the sample consisting of four cases, including two males and two females, which were psychologically ensured by cognitive behavioral therapy in parallel with the rehabilitation through a program of adapted physical activity and re-application of the test after a period Treatment, and this was in the psychological clinic of the Youth Institutions Office of Mostaganem. The results obtained showed a marked improvement in cases, a change in many negative thoughts, positive inclusion in society, and the mitigation of symptoms of psychological trauma and its override. The results were confirmed by statistical treatment, which included the Wilcoxen test and the Mann Whitney test, which They are considered non-parametric tests in place of the T test, for such studies. So, Statistical results indicated that there were differences between pre and post test in all cases in this study, gender differences in favor of females, and the absence of differences according to the variable of experience in the field of sports.
Keywords: الصدمة النفسية؛التكفل النفسي